Child Abdominal Trauma Due to Attack of Cattles While Working on Farms in Burkina Faso - Ouedraogo, Souleymane; Zaré, Cyprien; Zida, Maurice; Savadogo, Julien T.; Windsouri, Mamadou; Ouangre, Edgar; Bandre, Emile; Traore, Simon S. (Scientific Research, 2017)
Introduction: Cattle are strong animals very often used in agriculture in rural Africa. Unpredictable in their behavior, they regularly inflict injuries to farmers, some of whom are children in rural Africa. Objective: The purpose of this study was to describe the clinical, therapeutic and evolutionary aspects of abdominal trauma caused by bovidae to children on farms in Burkina Faso. Patients and Method: This is a descriptive study covering the period from January 2014 through December 2016 and was conducted in the General Surgery Unit of the Tenkodogo Regional Hospital in Burkina Faso. It included all patients under the age of 17, victims of abdominal trauma by cattle on farms. Result: A total of 68 patients were identified, which is 3% of all patients under 17 admitted to the service during the same period. The average age of patients was 10.5 years, with a standard variation of 3.6 years. The majority (73.5%) of the patients were boys. The main lesional mechanisms found were horn strokes (88.2%). We noted 35 eviscerations without visceral perforation, 15 intestinal perforations, 6 hepatic wounds and 5 splenic wounds. In 7 cases, there were non-penetrating wounds. All patients underwent surgical intervention under anesthesia. The average length of hospital was 6 days. Two deaths were recorded, making a mortality rate of 3%. Conclusion: Abdominal traumas of the child by attack of cattle are frequent during farm works in rural Burkina Faso. The injuries are sometimes serious. Wearing protective equipment for children should be considered during farm work.
Keywords: Abdominal Trauma; Cattle; Children; Field Work; Surgery